2015
DOI: 10.1007/jhep11(2015)054
|View full text |Cite
|
Sign up to set email alerts
|

EFT for vortices with dilaton-dependent localized flux

Abstract: Abstract:We study how codimension-two objects like vortices back-react gravitationally with their environment in theories (such as 4D or higher-dimensional supergravity) where the bulk is described by a dilaton-Maxwell-Einstein system. We do so both in the full theory, for which the vortex is an explicit classical 'fat brane' solution, and in the effective theory of 'point branes' appropriate when the vortices are much smaller than the scales of interest for their back-reaction (such as the transverse Kaluza-K… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(49 citation statements)
references
References 80 publications
(245 reference statements)
5
44
0
Order By: Relevance
“…Although extra-dimensional branes are not in themselves expected to be sufficient to provide a solution (for instance, one must also deal with the higher-dimensional cosmological constant), the techniques developed here can also be applied to their supersymmetric alternatives [42][43][44], for which higher-derivative cosmological constants are forbidden by supersymmetry and whose ultimate prospects remain open at this point. We make this application in a companion paper [45,46].…”
Section: Jhep11(2015)049mentioning
confidence: 99%
See 1 more Smart Citation
“…Although extra-dimensional branes are not in themselves expected to be sufficient to provide a solution (for instance, one must also deal with the higher-dimensional cosmological constant), the techniques developed here can also be applied to their supersymmetric alternatives [42][43][44], for which higher-derivative cosmological constants are forbidden by supersymmetry and whose ultimate prospects remain open at this point. We make this application in a companion paper [45,46].…”
Section: Jhep11(2015)049mentioning
confidence: 99%
“…Lastly, we plan [45,46] to also apply these techniques to a supersymmetric brane-world models that aim to tackle the cosmological constant problem [42][43][44]. The back-reaction of branes is a crucial ingredient of such models, and understanding the system in greater detail with an explicit UV completion will put these models on firmer ground and hopefully shed light on new angles from which to attack the CC problem.…”
Section: Jhep11(2015)049mentioning
confidence: 99%
“…This is important because the system often responds to perturbations by moving flux onto and off of the branes, since it is energetically inexpensive to change the value of φ. We use the effective theory that captures the low-energy dynamics of this flux in the higher-dimensional theorydeveloped in companion papers [1,2] -to work out the effective 4D description provided here, identifying in particular the precise form of the scalar potential that governs the energetics of vacuum determination. We find the following main results.…”
Section: Jhep10(2015)177mentioning
confidence: 99%
“…More recently [2] -see also [37,38] -it was found that the absence of dilaton couplings is not as straightforward as demanding dilaton-independence of the brane tension and BLF coefficient, A(φ), of (1.1), due…”
Section: Jhep10(2015)177mentioning
confidence: 99%
See 1 more Smart Citation